Determination of optimal conditions for electrodeposition of Tin(II) in the presence of Alizarin Red S. Issue 12 (December 2016) - Ali, Nour Mohammad-Sadik; Amaniampong, Prince Nana; Karam, Ayman
Abstract: A detailed physicochemical properties of aqueous solutions of alizarin red S − tin (II) chloride, has been thoroughly investigated by extensively exploring the effect of pH, concentration and temperature on the optimal conditions for the formation of tin (II)-alizarin red S (ARS-Sn II) complex. UV-Vis spectra, electrical conductivity and pH method were also used to characterize the final product. The stoichiometry of the reaction complex formation was determined via different referential methods. It was observed that, the reaction complex was formed when the concentrations were smaller than a certain limit (10 −5 M). Adjusting the pH of the reaction (typically from 3.7 to 6.0) also resulted in the formation of the complex. The formed complex was highly stable in dark conditions (absence of sunlight) and at ambient temperature. Without the use of additives and by employing the investigated optimal conditions (i.e. pH: 5.0, i: 6 mA/cm 2, t: 5 min, C: 0.1 M, d: 1.273 × 10 −4 cm), electrodeposition of tin (II) was demonstrated to be successful.